Comprehensive Management of Atopic Dermatitis in Adult Patients Using a Family Medicine Approach - Pratama, Radya Putra; Wibowo, Yudhi (Jurnal Ilmu Kedokteran Keluarga, 2024)
Background: Atopic dermatitis is a chronic inflammatory skin disease that is multifactorial. Its management requires a comprehensive approach involving the family. Objective: To discuss the comprehensive management of atopic dermatitis in an adult using a family medicine approach. Case: A 48-year-old man presented with itchiness and dry skin on the neck and arms since 1 month ago. He was diagnosed with atopic dermatitis based on William's criteria. Topical and systemic therapies, education, and trigger modification were carried out. Conclusion: A comprehensive approach with family medicine is important to ensure optimal diagnosis and therapy in cases of atopic dermatitis, one of which is through patient family education.